Customer preferences on high rise residential: The Mahogany Park Apartment / Muhammad Ammar Syafiq Mohd Yunus - Mohd Yunus, Muhammad Ammar Syafiq (Faculty of Business and Management, 2015)
High rise residential has emerged as a solution to the issues of land bank and the growing needs of residential properties. For one of the top developer in Malaysia, Sime Darby Property has developed an apartment called The Mahogany Park. Since it’s been launch on May 2014, the apartment has received slow and not very encouraging response from the public up until now. This has become an issue for the top developer namely Sime Darby Property in selling the said apartment. The main objective of this research is to identify, determine relationship and to evaluate the most significant factor (Location, Financial, Physical and Environment) that affect customer preference. There are many factors that affecting customer preference but in this study the researcher used variable from past researcher to support its research. By using convenience sampling technique, 100 questionnaires were distributed at Saujana Impian, Kajang to identify the real issues that curb this apartment. Analysis found that all the factor under discussion constitutes 97.4 % out of the factor that affect customer preference, financial factor is the most significant factor that contribute to the factors affecting the customer preference and this is supported by previous study and the finding in this study. This research is useful in guiding and serves as reference for housing developer and local government to fully understand house buyer’s expectation towards high rise residential, a good housing development project should be constantly revised to meets the wants and need of the customer.